1998
DOI: 10.1046/j.1469-8137.1998.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Cluster root development in Grevillea robusta (Proteaceae). I. Xylem, pericycle, cortex, and epidermis development in a determinate root

Abstract: (This paper is dedicated to the memory of Prof. Dr. Horst Marschner) The cluster roots of Grevillea robusta A. Cunn. ex R. Br. are composed of determinate rootlets that stop growing, but remain physiologically active for several months. Their apical organization, both before and after maturation, was studied by light and transmission electron microscopy. Each cell layer forms a dome, with an initial cell at its end. Xylem elements form a complicated triarch array at the base of the rootlet, passing alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…The morphology and anatomy of proteoid rootlets was reported previously for some members of the Proteaceae (for summary, see Dinkelaker et al, 1995;Skene et al, 1996Skene et al, , 1998aSkene et al, , 1998b. These studies showed that a cluster of rootlets starts as many meristematic primordia that subsequently mature into determinate rootlets with no apical meristem and root hairs around their tips.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…The morphology and anatomy of proteoid rootlets was reported previously for some members of the Proteaceae (for summary, see Dinkelaker et al, 1995;Skene et al, 1996Skene et al, , 1998aSkene et al, , 1998b. These studies showed that a cluster of rootlets starts as many meristematic primordia that subsequently mature into determinate rootlets with no apical meristem and root hairs around their tips.…”
mentioning
confidence: 64%
“…Determinacy has been reported in all species that form proteoid roots (Dinkelaker et al, 1995) but has also been observed in roots from other types of species (Varney and McCully, 1991;Dubrovsky, 1997). The average final length of a rootlet varies within and among proteoid species; recently Skene et al (1998a) showed that rootlets of Grevillea robusta were shorter when they developed in hydroponics compared with development in vermiculite. To our knowledge, we are the first to report that determinacy varies with environmental treatment ([CO 2 ]) in a common rooting medium (Fig.…”
Section: Synchronous Development Of Proteoid Rootsmentioning
confidence: 99%
“…Some have even been reported as having a normal epidermis but no cap, as in the orchid Pogonia (Carlson, 1938), and a few others derive their epidermis from a discrete meristem. In some dicots the epidermis might be the only layer of the cap complex of cells left intact in cultured roots (Skene et al, 1998). In both subclasses the affinity of the epidermis might be partially obscured in roots with open meristems because of instability of rates of cell division around the stelar pole (Clowes, 1981).…”
mentioning
confidence: 99%
“…One apical cell in the rootlet has undergone greater expansion than neighbouring cells and is breaking through the parental endodermis. This cell becomes the rootlet cap and epidermis initial (see also Skene et al (1998)). Later, a meristem forms, and a rootlet cap is visible (Fig.…”
Section: Endodermal Development In Juvenile Cluster Rootletsmentioning
confidence: 99%
“…ex R. Br. seedlings (Provenance Loitokitok, Kenya Forestry Seed Centre) were grown and prepared for light and transmission electron microscopy as described in Skene, Raven & Sprent (1998). Hand-cut sections through cluster roots were made by immobilizing roots in 1-cm$ pieces of polystyrene, and slicing with half of a double-edged razor blade.…”
Section: Plant Materialsmentioning
confidence: 99%